Grid Forming Operation for a High Step Ratio Modular Multilevel Dc-Dc Converter - Rojas-Lobos, F; Cerda-Jimenez, C (Institute of Electrical and Electronics Engineers Inc., 2020)
Recently, Modular Multilevel Converters (MMCs) have become an attractive solution for MV applications. MMCs can handle high voltage levels by interconnecting either full-or half-bridge converters in series, achieving high performance, modularity and excellent power quality. Although most of the reported MMC converters are proposed to interface AC voltages at least in one port, few topologies have been reported for direct DC-DC conversion, mainly intended for interconnection of two DC grids, focusing the most of the reports on the modulation and internal balancing of the converter. In this paper, the output voltage of a high-step ratio DC-DC MMC is controlled to operate as a grid forming converter. Simulation results show excellent performance of the converter, achieving internal voltage balancing and zero current switching operation(ZCS) under steady-state and transient response. © 2020 IEEE.